2003
DOI: 10.1093/nar/gkg646
|View full text |Cite
|
Sign up to set email alerts
|

The ERV-9 LTR enhancer is not blocked by the HS5 insulator and synthesizes through the HS5 site non-coding, long RNAs that regulate LTR enhancer function

Abstract: A solitary long terminal repeat (LTR) of ERV-9 human endogenous retrovirus is located upstream of the HS5 site in the human beta-globin locus control region and possesses unique enhancer activity in erythroid K562 cells. In cells transfected with plasmid LTR-HS5-epsilonp-GFP, the LTR enhancer activates the GFP reporter gene and is not blocked by the interposed HS5 site, which has been reported to have insulator function. The LTR enhancer initiates synthesis of long RNAs from the LTR promoter through the interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 55 publications
(53 reference statements)
1
22
0
Order By: Relevance
“…23 The ERV-9 LTR enhancer complex is active in stem/progenitor cells including erythroid progenitor cells; 34,35 it initiates synthesis of ERV-9 lncRNAs from the 5 0 end of the R region through the U5 region into the downstream genomic DNA to activate transcription of the globin genes by a long-range tracking and transcription mechanism. 36,37 In the current study, we found that the transcriptionally active ERV-9 LTR was >90% hypermethylated in erythroleukemia K562 cell line and primary human erythroblasts cultured from peripheral blood CD34C cells. Deletion of the ERV-9 LTR in K562 cells by CRISPR-Cas9 demonstrated that the hypermethylated ERV-9 LTR possessed in vivo function and activated transcription of the downstream globin genes.…”
Section: Introductionsupporting
confidence: 47%
See 3 more Smart Citations
“…23 The ERV-9 LTR enhancer complex is active in stem/progenitor cells including erythroid progenitor cells; 34,35 it initiates synthesis of ERV-9 lncRNAs from the 5 0 end of the R region through the U5 region into the downstream genomic DNA to activate transcription of the globin genes by a long-range tracking and transcription mechanism. 36,37 In the current study, we found that the transcriptionally active ERV-9 LTR was >90% hypermethylated in erythroleukemia K562 cell line and primary human erythroblasts cultured from peripheral blood CD34C cells. Deletion of the ERV-9 LTR in K562 cells by CRISPR-Cas9 demonstrated that the hypermethylated ERV-9 LTR possessed in vivo function and activated transcription of the downstream globin genes.…”
Section: Introductionsupporting
confidence: 47%
“…Although ERV-9 LTR enhancer function has been extensively characterized, 23,[35][36][37] the function of the neighboring CGI at the 5 0 border of the LTR remained unknown. It has been shown that the DNase hypersensitive HS4 site located at the 5 0 border of the chicken b-globin gene locus binds USF1 and CTCF and possesses strong insulator and barrier functions to protect the globin gene locus from epigenetic and transcriptional interference of flanking gene domains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent studies showed that this 5Ј HS5 ERV-9 LTR possesses prominent enhancer activity in embryonic and erythroid cell lines (16) and in oocytes and progenitor cells, including the erythroid progenitor cells, but not in differentiated somatic tissues in transgenic Zebrafish and humans (34). Unlike the HS2 and HS3 enhancers of the ␤-LCR, whose enhancer activities are blocked by the HS5 site with reported insulator properties when HS5 is interposed between the enhancer and the cis-linked promoter (35,36), the ERV-9 LTR enhancer is not blocked by the interposed HS5 site (37).…”
mentioning
confidence: 99%